2020
DOI: 10.1126/sciadv.aaz9014
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived porous nanomotor for thrombus therapy

Abstract: The treatment difficulties of venous thrombosis include short half-life, low utilization, and poor penetration of drugs at thrombus site. Here, we develop one kind of mesoporous/macroporous silica/platinum nanomotors with platelet membrane (PM) modification (MMNM/PM) for sequentially targeting delivery of thrombolytic and anticoagulant drugs for thrombus treatment. Regulated by the special proteins on PM, the nanomotors target the thrombus site and then PM can be ruptured under near-infrared (NIR) irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
174
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(175 citation statements)
references
References 47 publications
1
174
0
Order By: Relevance
“…[ 217 ] In vivo studies using near infrared powered nanorobot reported an increased efficacy urokinase toward thrombus therapy, when compared to passive delivery. [ 218 ] Chemically triggered microrobots do not require external stimuli to improve the therapeutic outcome. Therefore, they do not need expensive and bulky external systems commonly used for triggering other active delivery, such as occurring with previously described magnetic micromotors.…”
Section: Targeted Deliverymentioning
confidence: 99%
“…[ 217 ] In vivo studies using near infrared powered nanorobot reported an increased efficacy urokinase toward thrombus therapy, when compared to passive delivery. [ 218 ] Chemically triggered microrobots do not require external stimuli to improve the therapeutic outcome. Therefore, they do not need expensive and bulky external systems commonly used for triggering other active delivery, such as occurring with previously described magnetic micromotors.…”
Section: Targeted Deliverymentioning
confidence: 99%
“…The RBC morphology results showed that after incubation of Fe 3 O 4 @DMSA with RBCs, the RBCs still had the normal morphology ( Fig. S2B ), illustrating that Fe 3 O 4 @DMSA would not cause significant damage to RBCs [ 68 ]. Activated partial thromboplastin time/prothrombin time/thrombin time (APTT/PT/TT) results proved that Fe 3 O 4 @DMSA had no significant effect on the coagulation system compared with blank plasma ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[113] In addition to the autonomous motion, the intelligent micro/nanomotors with taxis facilitate themselves to deliver to areas that are not easy to target, such as thrombus sites and stomach. [100,114] Despite great potentials of micro/nanomotors, there are still many challenges in the future for biomedical applications.…”
Section: Discussionmentioning
confidence: 99%